The Effect Of T-STEM Designation On Charter Schools: A Longitudinal Examination Of Students' Mathematics Achievement - Ayse Tugba Oner; Robert M. Capraro; Mary Margaret Capraro (Sakarya University, 2016)
STEM interested students and graduates shape the future of a country. However, in the U.S., the number of STEM graduates was not sufficient; therefore, to increase this number, STEM school designation started. The number of STEM schools has been increasing and Texas was one of the states showing growth over time. STEM schools in Texas (T-STEM) were converted from different schools by specific procedures. The highest number of T-STEM conversion was from charter schools. The effectiveness of T-STEM charter schools compared to regular charter schools (non-T-STEM charter) was worth to examine because the number of T-STEM schools converted from charter schools was noteworthy. Moreover, the most important goal of T-STEM schools was to improve students' STEM achievement. In this study, to investigate the effectiveness of T-STEM charter schools, students' mathematics achievement over three years (through high school) was examined. There were 1481 participants in the study. To have comparable two groups, propensity score matching was used. After matching, hierarchical linear modeling was used to analyze students' mathematics achievement longitudinally considering student variables. The findings showed that T-STEM charter schools were effective to increase one minority group's (i.e. Hispanic students) mathematics achievement over time.